Un percorso esperienziale sugli stati di aggregazione della materia alla scuola dell’infanzia - Faramia, Jennifer (Chimica nella Scuola, 2025)
The following article reports on a teaching unit aimed at kindergarten children. The topic of the lessons concerns the three states of matter, which are presented to the students through manipulation experiences and small experiments that the children carry out personally in the classroom, with the constant support of the teacher.